Effect of planar optical guides on Cadmium Sulfide semiconductor films: CDS - Valera, Aníbal (2002)
In this work, we present the result of the application of Cadmium Sulfide Thin Film semiconductors as Planar Wave Guides. The experimental data of Wave Guide transversal transmission are complemented with spectral frontal transmission measurements to obtain a global explanationof this data As a secondary result of this analysis, we obrained finally the spectral dependence of the efective refraction index of CáS asa Thin Film material.